2021
DOI: 10.1021/acs.langmuir.1c00338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Chemical and Structural Properties of Silane Monolayers on the Organization of Water Molecules and Ions at Interfaces, from Molecular Dynamics Simulations

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Regarding the surface, the amorphous SiO 2 layer was taken from the study of Roscioni et al and resized to the simulation box dimensions with a 2 nm thickness by a homemade Python code. Silane monolayers were built following our process adapted from the method proposed by Roscioni et al, as we have previously described. ,, Shortly, hydrolyzed silane molecules were initially randomly positioned on the silica (SiO 2 ) surface without using explicit bonding, allowing for their spontaneous lateral organization. Six different silane monolayers were designed, all with a surface coverage of 3.0 nm –2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the surface, the amorphous SiO 2 layer was taken from the study of Roscioni et al and resized to the simulation box dimensions with a 2 nm thickness by a homemade Python code. Silane monolayers were built following our process adapted from the method proposed by Roscioni et al, as we have previously described. ,, Shortly, hydrolyzed silane molecules were initially randomly positioned on the silica (SiO 2 ) surface without using explicit bonding, allowing for their spontaneous lateral organization. Six different silane monolayers were designed, all with a surface coverage of 3.0 nm –2 .…”
Section: Methodsmentioning
confidence: 99%
“…Silane monolayers were built following our process adapted from the method proposed by Roscioni et al 21 , as we have previously described. 19,22,23 Shortly, hydrolyzed silane molecules were initially randomly positioned on the silica (SiO 2 ) surface without using explicit bonding, allowing their spontaneous lateral organization. Six different silane monolayers were designed, all with a Secondary structure of the ACE2 -S-RBD complex.…”
mentioning
confidence: 99%
“…MMT surface’s high negative charge (−628e) is balanced by the presence of positively charged ions (Na + , Ca 2+ ). The presence of ionic species is known to influence protein–surface interaction. ,, To quantify the extent of ion-surface interaction, we evaluated the contact frequency of ions with the surface. Figure c shows the number of ions and the corresponding percentage of contact frequency with the MMT surface for Na-MMT and Ca-MMT systems.…”
Section: Nature Of Protein–surface Interaction and Influence Of Count...mentioning
confidence: 99%
“…Despite the common use and the growing interest in SA/biotin technology, the understanding of the parameters that define the stability and orientation of SA on biotinylated surfaces is very limited (Migliorini et al, 2014;Osypova et al, 2015) since the corresponding orientation of SA on the surface can rarely be confirmed by experiments. Several macroscopic parameters such as chain length, charge of the head group of linker molecules are known (Lecot et al, 2020) to impact conformational fluctuations of Streptavidin while immobilizing over the surface and hence affecting biotin binding. Furthermore, a recent AFM and Steered Molecular Dynamics (SMD) study (Sedlak et al, 2020) highlighted the differences in an unbinding pathway with 4-fold different unbinding forces in pulling out biotin molecules from 4 different subunits of Streptavidin; in particular, owing to the tethered geometry of the linker molecule, the conformational changes of the biotin-binding loop of Streptavidin is affected differently for different monomeric units thus leading to potential discrepancy in the escaping mechanism of biotin.…”
Section: Introductionmentioning
confidence: 99%